Pengaruh Struktur Kepemilikan, Debt Maturity, dan Kualitas Laporan Keuangan Terhadap Efisiensi Investasi - Raisah Nur Hotimah; Uswatun Khasanah; Triana Yuniati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to examine and analyze the influence of ownership structure, debt maturity, and financial reporting quality on investment efficiency in energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. This research employs a quantitative research method using secondary data obtained from the companies' annual financial statements. The population of this study consists of all energy sector companies listed on the Indonesia Stock Exchange during the specified period, with samples selected using a purposive sampling technique based on specific criteria, resulting in a total of 105 samples. The analytical methods used include descriptive statistical tests, classical assumption tests, and multiple linear regression analysis to test the hypotheses. The results of this study indicate that: (1) ownership structure, as measured by institutional ownership, has a positive and significant relationship with investment efficiency, while managerial ownership has no effect on investment efficiency; (2) debt maturity has a positive and significant relationship with investment efficiency; (3) financial reporting quality has no effect on investment efficiency. These findings provide theoretical and practical contributions to understanding the factors influencing investment efficiency in energy sector companies in Indonesia.